2006
DOI: 10.1016/j.cis.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Importance of physical vs. chemical interactions in surface shear rheology

Abstract: The stability of adsorbed protein layers against deformation has in literature been attributed to the formation of a continuous gel-like network. This hypothesis is mostly based on measurements of the increase of the surface shear elasticity with time. For several proteins this increase has been attributed to the formation of intermolecular disulfide bridges between adsorbed proteins. However, according to an alternative model the shear elasticity results from the low mobility of the densely packed proteins. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…Whether the aggregates participate to interfacial film viscoelasticity via disulfide bonds formation cannot be excluded, but it probably play a secondary role as the number of exposed sulfhydryl groups (accessible to DTNB) is more or less independent of the heating time at 80 • C while the shear elastic constant at the plateau was significantly lower. This confirms the results obtained by Wierenga et al [30] showing that introduction of reactive sulfhydryl groups on the surface of ovalbumin molecule did not lead to increased shear elastic constant. In addition, the decreased of the shear elastic constant at the plateau value with prolonged heating time from 5 to 40 min at 80 • C while neither the kinetics of formation of intermolecular interactions in the interfacial layer nor the foam stability was modified indicated that the shear elastic constant at the plateau value does not constitute the most prevalent criteria to predict the foam stability of protein dispersions confirming previous results we obtained studying the interfacial properties of non-native structures of β-lactoglobulin.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Whether the aggregates participate to interfacial film viscoelasticity via disulfide bonds formation cannot be excluded, but it probably play a secondary role as the number of exposed sulfhydryl groups (accessible to DTNB) is more or less independent of the heating time at 80 • C while the shear elastic constant at the plateau was significantly lower. This confirms the results obtained by Wierenga et al [30] showing that introduction of reactive sulfhydryl groups on the surface of ovalbumin molecule did not lead to increased shear elastic constant. In addition, the decreased of the shear elastic constant at the plateau value with prolonged heating time from 5 to 40 min at 80 • C while neither the kinetics of formation of intermolecular interactions in the interfacial layer nor the foam stability was modified indicated that the shear elastic constant at the plateau value does not constitute the most prevalent criteria to predict the foam stability of protein dispersions confirming previous results we obtained studying the interfacial properties of non-native structures of β-lactoglobulin.…”
Section: Discussionsupporting
confidence: 94%
“…5 gives the values recorded at equilibrium, 10 h after the beginning of absorption. Note that these values remained constant as soon as [30] and Pezennec et al [4] for the same protein concentration in the bulk (100 µg mL −1 ) and for pH conditions far from ovalbumin pI. These values are in the range for a monolayer of protein adsorbed at the air/water interface.…”
Section: Interfacial Properties Of the Heat-treated Solutions Of Ovalmentioning
confidence: 90%
“…For β-lactoglobulin, the evidence points towards the fact that the surface layer is a physically jammed state for surface pressures above ∼10 mN/m. This is supported by the similarity of viscoelastic data between 2D hard colloids and β-lactoglobulin layers [12], by the fact that the threshold concentration for emergence of a shear modulus is so high [11], and finally by very recent experiments where the presence or absence of chemically active groups was shown not to play an important role [36].…”
Section: Fluid and Soft Solid Surface Layersmentioning
confidence: 71%
“…While nearly no sub-phase corrections are required for the data measured using the DWR geometry, in other instruments used for making interfacial measurements with lower characteristic values of the Boussinesq numbers, the sub-phase contributions to the torque must be carefully accounted for (see, for example, the papers by Mannheimer and Schechter 33 and Oh and Slattery 34 . Several studies 3,4,31,35 have noted the long time scales required for adsorbed interfacial layers to reach equilibrium, with Wierenga et al 35 waiting for as long as 24 hours. This effect is even more pronounced in surfactant-protein mixtures 31,36 .…”
Section: Methodsmentioning
confidence: 99%